Implementing positive organizational change : a strategic project management approach - Abudi, Gina (J. Ross Publishing, 2017)
With examples, tips, and mini case studies, this book explains how to develop a continuous improvement culture of change that will be perceived by employees as a positive opportunity to create something new, exciting and valuable, instead of something negative to confront and resist. --